Mitigating Risk in The Construction Supply Chain Through the Integration of The Supply Chain Operations Reference Model and the House of Risk Method - Achmad Bahauddin; Ratna Ekawati; Hilal Yumna; Atia Sonda; Christine Natalia (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: During construction, companies face various risks that can disrupt operational efficiency. Potential risks include payment schemes that do not align with the initial contract, errors in estimating material requirements, and inaccuracies in work planning.Purpose: This study focuses on identifying risk events and risk agents within the construction supply chain process, determining the priority of risk agents based on Aggregate Risk Potentials (ARP), and proposing mitigation strategies to address these risk agents.Design/methodology/approach: This research employs the Supply Chain Operations Reference (SCOR) 11.0 model and the House of Risk (HOR) method, utilizing Phase 1 for risk identification and Phase 2 for determining actions to mitigate the identified risk sources.Findings/Results: Seventeen risk agents and sixteen risk events were identified. The priority risk agents include a payment system that deviates from the initial contract, inaccuracies in estimating material requirements, and errors in work planning calculations. In response to these risks, five risk mitigation strategies were proposed: (1) estimating unexpected costs, (2) establishing an alternative payment system, (3) formulating Standard Operating Procedures for material specifications, (4) forecasting material prices, and (5) creating an automated system for estimating labor requirements.Conclusion: In the construction supply chain, among the identified risk events and risk agents, the top-priority risk agents include payment schemes that do not align with the initial contract, inaccuracies in calculating material requirements, and errors in work planning calculations. These results show that risks associated with money, materials, and planning are very important for making the building supply chain less effective. Combining SCOR and the HOR method provides an organized, data-driven approach to identify, rank, and reduce risks in a methodical manner. In practice, the results help businesses better allocate resources, reduce project delays, and keep costs down by using focused and proactive risk management measures.Originality/value (State of the art): This study contributes to the existing literature by developing a hybrid risk management framework by integrating the SCOR model with the HOR method, enabling systematic mapping and assessment of risks across the entire construction supply chain.  Keywords:  risk mitigation, house of risk, supply chain operations reference, construction supply chain, supply chain management